Genetics, epigenetics and transgenerational transmission of obesity in children - Panera, Nadia; Mandato, Claudia; Crudele, Annalisa; Bertrando, Sara; Vajro, Pietro; Alisi, Anna (Frontiers in Endocrinology, 2022)
Sedentary lifestyle and consumption of high-calorie foods have caused a relentless increase of overweight and obesity prevalence at all ages. Its presently epidemic proportion is disquieting due to the tight relationship of obesity with metabolic syndrome and several other comorbidities which do call for urgent workarounds. The usual ineffectiveness of present therapies and failure of prevention campaigns triggered overtime a number of research studies which have unveiled some relevant aspects of obesity genetic and epigenetic inheritable profiles. These findings are revealing extremely precious mainly to serve as a likely extra arrow to allow the clinician’s bow to achieve still hitherto unmet preventive goals. Evidence now exists that maternal obesity/overnutrition during pregnancy and lactation convincingly appears associated with several disorders in the offspring independently of the transmission of a purely genetic predisposition. Even the pre-conception direct exposure of either father or mother gametes to environmental factors can reprogram the epigenetic architecture of cells. Such phenomena lie behind the transfer of the obesity susceptibility to future generations through a mechanism of epigenetic inheritance. Moreover, a growing number of studies suggests that several environmental factors such as maternal malnutrition, hypoxia, and exposure to excess hormones and endocrine disruptors during pregnancy and the early postnatal period may play critical roles in programming childhood adipose tissue and obesity. A deeper understanding of how inherited genetics and epigenetics may generate an obesogenic environment at pediatric age might strengthen our knowledge about pathogenetic mechanisms and improve the clinical management of patients. Therefore, in this narrative review, we attempt to provide a general overview of the contribution of heritable genetic and epigenetic patterns to the obesity susceptibility in children, placing a particular emphasis on the mother-child dyad.